TPS 3R Management Development Model: Social Learning, Collaboration and Partnership, Zero Waste Lifestyle for a Sustainable Future - Firmansyah, Deri; Suryana, Asep; Rifai, Asep Achmad; Hartika, Nely; Syamiya, Estu Niana (PT. Riset Press International, 2024)
The implementation of PKM as a critical concern related to the classic problem of waste disposal. The text of this article is a synthesis of reports from two community service (PKM) implementations carried out continuously in two academic periods, regarding the issue of developing TPS 3R management and the dominance of household waste composition. The results of the implementation of the first edition of PKM and the second edition of PKM based on social learning, coolaboration and partnership consistently lead to a zero waste lifestyle in the future in a sustainable manner. Small surveys, conservation and socialization are part of the methodological aspects of both PKM implementation, social learning, environment, dynamic interaction and community learning methods are adopted, future expectations of the results of the implementation are both synthesized. To improve sustainable waste management, the TPS3R management development model is based on social learning through collaboration and partnership minimization towards zero waste by involving four actors (quadruple helix) who consider social and environmental elements in an innovative collaboration framework, relevant to be adopted, implemented and developed, towards a zero waste lifestyle in a sustainable future. The aspects needed to achieve the success of this process emphasize several keyword aspects, including socialization, culture, awareness, consumtion pattern (smart consumer), wise lifestyle, mindset, social learning, adaptive & innovative, immitation &; evaluative models, consistency.